Common bean (Phaseolus vulgaris L.) yield response to chemical and biological fertilization in different localities of Colombia (2018)
The research was carried out in 2015 in five bean producing locations in Colombia. The objective was to evaluate the effect of different treatments of chemical and biological fertilization on the yield of climbing and bush beans. According to the results obtained, in Antioquia, it is possible to replace the chemical fertilization by biological fertilization in the climbing bean Corpoica LAS-106 and the bush bean Citará. In Cundinamarca, similar situation was presented with “Cargamanto Rojo”. In Santander, it was found that the combination of mycorrhizae (AMF) and Rhizobium improves the performance of the bush bean ICA-Rovirense (2839.5 t ha-1) and ICA-Radical-J1J1 (1955.7 t ha-1), with respect to national average yield (1.2 t ha-1). The use of biofertilizers (mycorrhizal fungi and Rhizobium) improved the yields in the bean crop, with the materials used (climbing and bush) and in the localities studied.There is an additive effect in the applications of the biofertilizers evaluated, since it is a higher yield in the bean crop when these were applied individually combined.